O7 Simulation@Distance – Exploring Remote Alternatives to Traditional Clinical Simulation Training. (10th November 2020) - Gumble, Eli; Broughton, Emma
Abstract : Introduction: The social distancing guidelines brought about in response to the COVID-19 pandemic made the normal operation of a simulation centre with limited floor space impossible. To continue providing training to a greater number of candidates, some methods for recreating the simulation experience with remote candidates were devised and explored. Methods: Proposal A: Conversational avatar over Zoom. Through use of OBS Studio streaming software, our pre-existing conversational avatar is presented on a Zoom call for remotely-connected candidates to interact with for conversational simulation. Proposal B: Gameplay style scenarios on CenarioVR shared with candidates. Candidates (alone or in groups, with or without supervision) navigate a clinical room environment with buttons and menus to undertake a scenario, with the system keeping track of events to progress the scenario along. Proposal C: Remote In-Ear (RIE) coaching. Through use of a wireless earbud, candidates communicate remotely with centre staff ('operatives') who follow the instructions given to them by candidates watching a live Zoom feed of the room. 3 ways of achieving this were explored: C1: Candidates remotely watch a feed of the simulation room while connected to an operative by an audio call. C2: Candidates message their target operative on Zoom and text-to-speech software reads these messages to the operatives. C3: Zoom breakout rooms/separate WhatsApp video calls connect candidates to target operatives, where candidates see from the operative's perspective through a head-mounted camera. Proposal D: Virtual environments D1: Candidates meet in a private World within VRChat for scenarios. D2: Candidates meet in the Minecraft server containing a pre-existing replica of the hospital for scenarios. Results: Proposals were scored 0–40 for viability, summed from 0–10 scores in 4 categories: Team Interactivity, Fidelity, Range of Scenarios and Ease of Implementation. These scores are shown in Simulation@Distance table 1 . Discussion and Conclusions: So far, the options judged to be most viable have been trialled. The avatar's use over Zoom proved to be easy to set up and once we find suitable faculty to run it, courses will be arranged and advertised. RIE coaching has had trial sessions, with operatives initially reporting inefficiencies in communication. In response to the feedback, the model has been revised so that the wider group are now coaching the whole room as opposed to individual candidates. The gameplay scenarios are still being worked on, but externally produced alternatives are being explored. Overall, we are confident that simulation can coexist with distancing guidelines.